Efectividad de los brackets autoligados versus brackets convencionales en el tratamiento del apiñamiento dental - Juan Esteban, Pérez Arias (2021)
ABSTRACT The purpose of the present study was to analyze the different clinical characteristics, properties, advantages and limitations between self-ligating brackets and conventional braces in the treatment of dental crowding, by means of a bibliographic review of articles published in the last 10 years, from databases of data such as Google Scholar, Pubmed, Elsevier, and Springer Link. Eighty articles were collected, of which those with an average ACC citation count and SJR impact factor were selected, from which 60 scientific articles were finally obtained for systematic review. After reviewing the literature, it was found that the main properties of self-ligating brackets were to be safe and robust, to ensure complete engagement of the arch support, to have low friction between the support and the arch, to allow high friction and easy clamping of the arch support. the elastic chain, maintain good oral hygiene and be comfortable for the patient. The only evidence-based advantages of self-ligating brackets were the reduction in working time in the dental chair and the control of the pro-inclination of the mandibular incisors, no other significant differences were found in the treatment time or occlusal characteristics. There were not enough studies to corroborate the effectiveness of self-ligating braces over conventional braces with significant clinical evidence in the treatment of dental crowding, it is possible that the popularity of these self-ligating systems is due to effective marketing and advertising. Key words: self-ligating brackets, conventional brackets, dental crowding. Reviewed by: MsC. Adriana Cundar, PhD. ENGLISH PROFESSOR c.c. 1709268534